2015
DOI: 10.1186/s13104-015-1528-7
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of patients with psychosis: a systematic review

Abstract: BackgroundSocial networks are important for mental health outcomes as they can mobilise resources and help individuals to cope with social stressors. Individuals with psychosis may have specific difficulties in establishing and maintaining social relationships which impacts on their well-being and quality of life. There has been a growing interest in developing social network interventions for patients with psychotic disorders. A systematic literature review was conducted to investigate the size of social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 47 publications
8
75
2
Order By: Relevance
“…The social networks of patients in this study were small: a mean of 10.2 individuals. This is remarkably close to the figure of 11.7 reported in a recent systematic review of the social networks of patients with psychotic illnesses [36]. We found that relatives made up 42% of these contacts, very close to the systematic review figure of 43.1%.…”
Section: Discussionsupporting
confidence: 90%
“…The social networks of patients in this study were small: a mean of 10.2 individuals. This is remarkably close to the figure of 11.7 reported in a recent systematic review of the social networks of patients with psychotic illnesses [36]. We found that relatives made up 42% of these contacts, very close to the systematic review figure of 43.1%.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, loneliness is associated with poorer quality of life [17] and personal recovery [18], and with more severe mental health symptoms [19]. Similarly, a number of negative health outcomes have been found to be associated with objective social isolation, for example, increased all-cause mortality rate [20], poor physical health outcomes [21,22], worse psychotic symptoms [23,24], depressive symptoms [24], and higher risk of dementia [25]. Conversely, social support that is perceived as sufficient is associated with less severe psychiatric symptoms, higher functioning, better personal recovery, greater self-esteem and empowerment, and improved quality of life [26].…”
Section: Introductionmentioning
confidence: 99%
“…Older women with schizophrenia have also accumulated physical health risks as a result of their illness, their life style and perhaps also as a result of long exposure to antipsychotic drugs . However, it is also possible that younger women with schizophrenia had higher levels of social support than older women, a hypothesis that is supported by schizophrenia literature suggesting that family support tends to decline with length of illness . It is also possible that adolescent mothers with schizophrenia had access to more comprehensive support from formal supports and services such as could be offered in comprehensive first‐episode psychosis programmes, and/or from public health nursing that mitigated their risk for psychiatric crises requiring admission.…”
Section: Discussionmentioning
confidence: 99%